Chapter 6 Perceived religious discrimination in healthcare A qualitative study of formal complaints - Enstedt, Daniel; Dellenborg, Lisen (Taylor & Francis, 2024)
Swedish healthcare providers must comply with the Patient Act's principles of equal and accessible care and account for patients' religious backgrounds by offering culturally sensitive care. This chapter explores what characterizes patients' and their relatives' expectations in healthcare encounters perceived as religiously discriminatory in the diverse Swedish healthcare system. It analyses perceived religious discrimination in healthcare through the interpretative phenomenological analysis of complaints submitted to the Equality Ombudsman in Sweden from 2012 to 2021, which registered 92 complaints as religious discrimination in healthcare, 66 of which were included in this study's analytical sample. The complaints addressed unfulfilled expectations related to cultural and religious literacy, equal treatment in relation to religious symbols or medical records, affirmative action in medical treatment that takes beliefs into account, and a secular environment that forbids religious symbols in healthcare encounters. One-third of the complaints were submitted by Muslims or individuals presumed to be Muslim. Several complaints concerned healthcare providers' reactions to patients wearing hijabs or other ethnic or religious attributes. The study indicates that healthcare providers face difficulties in conforming to the partially contradictory ideals of equal treatment and cultural sensitivity, whose relation to religious diversity has not yet been clearly defined.